Reversible Perspiring Artificial “Fingertips” - Zhang, Dongyu; Peixoto, Jacques; Zhan, Yuanyuan; Astam, Mert O.; Bus, Tom; van der Tol, Joost J. B.; Broer, Dirk J.; Liu, Danqing (Advanced materials (Weinheim), 2023)
Fingertip perspiration is a vital process within human predation, to which the species owes its survival and its biological success. In this paper, the unique human ability of extensive perspiration and controlled friction in self‐assembled cholesteric liquid crystals is recreated, mimicking the natural processes that occur in the dermis and epidermis of human skin. This is achieved by inducing porosity in responsive, liquid‐bearing material through the controlled‐polymerization phase‐separation process. The unique topography of human fingerprints is further emulated in the materials by balancing the parallel chirality‐induced force and the perpendicular substrate‐anchoring force during synthesis. As a result, artificial fingertips are capable of secreting and re‐absorbing liquid upon light illumination. By demonstrating the function of the soft material in a tribological aspect, it exhibits a controllable anti‐sliding property comparable to human fingertips and subsequently attains a higher degree of biomimicry. This biomimetic fingertip is envisioned being applied in a multitude of fields, ranging from biomedical instruments to interactive, human‐like soft robotic devices. Here, a coating made of liquid crystal networks is designed to mimic not only the unique fingerprint topography, but also the liquid secretion in human fingertips. The biomimetic perspiration of the coating is reversible as controlled by light, which can be used to fine‐tune the tribological property when the coating is in contact with other surfaces.